2013
DOI: 10.1002/2013jc009160
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of extreme sea levels over the eastern continental shelf of North America

Abstract: [1] This study presents distributions of extreme sea levels over the eastern continental shelf of North America (ECSNA) associated with storm surges and tidal surface elevations produced by a 2-D ocean circulation model for the period 1979-2010. The 2-D circulation model is driven by atmospheric and tidal forcing. The large-scale atmospheric forcing is the wind stress and sea level atmospheric pressures extracted from NCEP (National Centers for Environmental Prediction) Climate Forecast System Reanalysis (CFSR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Based on the balance between the accuracy and computational cost of the models used in our previous studies, we have selected a resolution between 1 and 100 km for the present study. The selected mesh resolution at the coast (∼1 km) and in the surf zone and shallow waters (i.e., water depth of 20 m or less) is an improvement compared to the resolution of computational meshes used in the previous basin‐scale studies (e.g., ∼ 5–7 km in Zhang and Sheng, ; ∼5 km in Muis et al, ). A finer mesh may improve the model accuracy but can increase the computational demand, which is not optimal for simulating a large number of historical storms in the present study and tens of thousands of synthetic storms in our subsequent basin‐scale flood hazard assessment study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the balance between the accuracy and computational cost of the models used in our previous studies, we have selected a resolution between 1 and 100 km for the present study. The selected mesh resolution at the coast (∼1 km) and in the surf zone and shallow waters (i.e., water depth of 20 m or less) is an improvement compared to the resolution of computational meshes used in the previous basin‐scale studies (e.g., ∼ 5–7 km in Zhang and Sheng, ; ∼5 km in Muis et al, ). A finer mesh may improve the model accuracy but can increase the computational demand, which is not optimal for simulating a large number of historical storms in the present study and tens of thousands of synthetic storms in our subsequent basin‐scale flood hazard assessment study.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a few basin‐scale studies have been carried out to simulate a large number of historical storms and to present storm surge hazards over the entire basin. For example, Zhang and Sheng () presented the spatial distribution of water levels induced by tropical and extratropical cyclones over the eastern continental shelf of North America. They used the two‐dimensional (2‐D) depth‐averaged version of Princeton Ocean Model (POM), with a horizontal resolution of about 5–7 km, to simulate astronomical tides and storm surges during a 31 year period between 1979 and 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several extreme value analysis techniques were developed to estimate the return periods of extreme sea levels (Bernardara;Andreewsky and Benoit, 2011;Kim, 2010, 2012;Woodworth and Blackman, 2002). Many studies have suggested the use of the GEV approach to estimate the extreme sea levels (Kim et al, 2016;Zhang and Sheng, 2013). Before applying NSFA, the data should be tested against trends or changes/shifts in the mean and variability in order to assess its stationarity or the nonstationarity (Hawkes et al, 2008).…”
Section: Nonstationary Frequency Analysis (Nsfa)mentioning
confidence: 99%
“…The Gumbel model parameters and 50-year return levels for all tide-gauge stations show large spatial variations for Atlantic Canada (Table 3). The location parameter is equal to the (Bernier & Thompson, 2006;Zhang & Sheng, 2013). A smaller-scale parameter indicates that the return period is sensitive to small changes in mean SLR.…”
Section: B Statistics Of Extreme Water Levelsmentioning
confidence: 99%